If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 9 + -9x = 18 + -16x Solving 9 + -9x = 18 + -16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16x' to each side of the equation. 9 + -9x + 16x = 18 + -16x + 16x Combine like terms: -9x + 16x = 7x 9 + 7x = 18 + -16x + 16x Combine like terms: -16x + 16x = 0 9 + 7x = 18 + 0 9 + 7x = 18 Add '-9' to each side of the equation. 9 + -9 + 7x = 18 + -9 Combine like terms: 9 + -9 = 0 0 + 7x = 18 + -9 7x = 18 + -9 Combine like terms: 18 + -9 = 9 7x = 9 Divide each side by '7'. x = 1.285714286 Simplifying x = 1.285714286

| 121x^2-144=0 | | -14-2x=11-7x | | 7-6x=55 | | 8x(x-6)=0 | | 5n-7=28 | | 20+15d=33+28d | | 62-3x=6x+16 | | 8(n+7)=32+2n | | 2x+40=84 | | 14=m-10 | | 7+x-7x= | | 2(n-4)+3= | | X^2+6x+20=0 | | 7-5a=52 | | 8y=98+65 | | 8-(-8)+9y=7 | | 52-28u=52 | | 9x+14=19+4x | | 14x-12=10x-12 | | -6x+5=7 | | 11x-13=119 | | 16x^2+10x+100=0 | | 5e-4=30.5 | | 5-3h=20 | | -16x^2+10x+100=0 | | m-6=103 | | 6x+4=-2x+100 | | -16x^2-10x+100=0 | | 11x-23=98 | | -24=6a-15-5 | | 2x=y+3 | | 27.6=6c-3 | | 36+n=9 | | 4z-28=35 | | 36+n=-9 | | 4(a+4)=23.6 | | 3x^2=14x+5 | | 5(x-3)=6.5 | | 14x^2+30x+4=0 | | -7x-3=-59+7x | | 4x-1=11x-78 | | 9c-27=29+2c | | 16x^2-30x+1=0 | | 13p+15q=89 | | 0.05-0.01y=04 | | -2m+5=11 | | -6x+2y=2 | | x(x-4)-14=130-4x | | 9x^2-18x-27=0 | | 5x^2+X+2=0 | | 21=6r+5-r | | (4ab)(5a^2b^3)= | | 2y^2-9y+18=0 | | -4x+3y=-2 | | 0.05x+0.27-0.01y+0.15y=0.4+14.4 | | -2m=-2 | | -13-3x=11-3x | | 0=-5y^2+24+48 | | 0=-5y^2+24y+48 | | 5x^2+11x+2=0 | | -92-9x=10x+22 | | 2k+k+3k= | | x^2+x-42=0 | | 27x-3(x-6)=6 | | 5-8x=71-29x |